Performance Management Concept Framework of The Corruption Eradication Commission (KPK) in Optimizing State Loss Recovery - Taryanto Taryanto; Eko Prasojo (Universitas Sultan Ageng Tirtayasa, 2021)
The performance of the Corruption Eradication Commission (KPK) has always been in the public spotlight, so significant research has been carried out, especially on one of the performance indicators that has become a public issue, namely how the KPK has performed in recovering state losses. Starting from this background, the purpose of this study is to develop a conceptual framework for the performance management of the corruption eradication commission in optimizing the recovery of state losses. The conceptual framework is based on the theory of performance management or performance management (PMS), using the dimensions of the balanced scoring model Niven (2008) which is sliced with the BSC model of Moullin (2017) and model of Aydin (2019), and operationalized with indicators, where most of these indicators have so far also been used as indicators for measuring KPK's performance. The framework of the performance management concept of the corruption eradication commission in optimizing the recovery of state losses can be the basis for researchers when they want to examine the performance of the KPK in the context of optimizing the recovery of state losses.